Kualitas Ikan Gabus (Channa striata) Asap yang Dibuat dengan Alat dan Sumber Asap yang Berbeda - Hali Murdani; Agus Supriadi; Susi Lestari (Universitas Sriwijaya, 2016)
This study attempts to know the quality of snakehead (Channa striata) being smoked by tools with different resources of the smoke. This study was conducted from April 2015 until May 2015 in Complex Independent Kayu Agung, Bioprocess Laboratory of Chemical Engineering, Faculty of Engineering, Technology Laboratory of Fisheries, Faculty of Agriculture, University of Sriwijaya, and the Central Laboratory of Agro Industry Bogor. The method used is a randomized block design factorial (RAKF). This research used treatment were tools (system cabinet, conventional systems) and resources of the smoke (wood-fighting, shell). The parameters observed were proximate analysis (moisture content, protein content, fat content, ash content, carbohydrate content) levels of benzo[a]pyrene and benzo[a]anthracene. Based on the test design randomized factorial (RAKF), treatment of tools with different resources of the smoke (p>0.05) showed the results of analysis of water content, protein content, fat content varies for each treatment, while ash and carbohydrate content showed the results is not different for each treatment. The observation of the levels benzo[a]pyrene analysis on smoked snakehead (Channa sriata) (p>0.05) showed different results for each treatment and results of benzo[a]anthracene analysis showed different for each treatment. The results of analysis of benzo[a]pyrene was below the maximum threshold of Indonesian National Standard, FAO and WHO.